The Role of Volcanic Activity in Climate and Global Change - Stenchikov, Georgiy L. (Elsevier BV, 2015)
Explosive volcanic eruptions are magnificent events that in many ways affect the Earth's natural processes and climate. They cause sporadic perturbations of the planet's energy balance, activating complex climate feedbacks and providing unique opportunities to better quantify those processes. We know that explosive eruptions cause cooling in the atmosphere for a few years, but we have just recently realized that volcanic signals can be seen in the subsurface ocean for decades. The volcanic forcing of the previous two centuries offsets the ocean heat uptake and diminishes global warming by about 30%. The explosive volcanism of the twenty-first century is unlikely to either cause any significant climate signal or to delay the pace of global warming. The recent interest in dynamic, microphysical, chemical, and climate impacts of volcanic eruptions is also excited by the fact that these impacts provide a natural analogue for climate geoengineering schemes involving deliberate development of an artificial aerosol layer in the lower stratosphere to counteract global warming. In this chapter we aim to discuss these recently discovered volcanic effects and specifically pay attention to how we can learn about the hidden Earth-system mechanisms activated by explosive volcanic eruptions. To demonstrate these effects we use our own model results when possible along with available observations, as well as review closely related recent publications.